An Energy Efficient Cluster based Load Balancing Algorithm Applied in Cloud Computing - Banerjee, Annwesha; V, Sourav; Pal, Shubham; Putatunda, Alap (International Journal of Computer Sciences and Engineering, 2020)
In this paper we have proposed an energy efficient load balancing algorithm for cloud computing. This proposed algorithm categorized the virtual machines and the queued jobs in HIGH, MEDIUM and LOW clusters considering different criteria, jobs would be assigned accordingly to competent virtual machines. The proposed algorithm is considering battery power also for categorize its cluster, which promotes it as energy efficient algorithm.